COSMIC SILENCE AND HUMAN SOLITUDE IN ALEKSANDR FAYNBERG’S POETIC IMAGERY (Ustozlar uchun, 2025)
This article offers an in-depth literary analysis of Aleksandr Faynberg’s poem depicting a solitary fisherman beneath the night sky. Through symbolic imagery of stars, moonlight, silence, and motionless water, the poet creates a philosophical reflection on human solitude, creative contemplation, and the fragile boundary between reality and imagination. The study explores the poem’s symbolic system, lyrical subject, metaphysical dimension, and aesthetic value, situating it within Faynberg’s broader poetic worldview. The analysis emphasizes how cosmic elements interact with human presence, transforming an ordinary scene into a timeless meditation on existence, inner silence, and spiritual richness.